Comportamiento del diámetro y altura total en las plantas de Cedrelinga cateniformis Ducke con diferentes dosis de abonamiento foliar en plantación. Puerto Almendra, Loreto Perú - 2022 - Vargas Piña, Maria Ines (2023)
The research work was carried out in a CIEFOR Puerto Almendra - FCF - UNAP plantation, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine if there is a significant difference in the growth in diameter and total height in the Cedrelinga cateniformis Ducke "tornillo" plants with different doses and frequencies of foliar fertilization in the plantation, Puerto Almendra, Loreto, Peru - 2021. In the study, used the completely randomized block design fixed to the factorial experiment considering as factor "A" the fertilization dose with levels a0 = 20 ml; a1 = 40 ml and a2 = 60 ml and, as factor "B" to the frequency of fumigation of the fertilizer with levels b0 = 1 time per week; b1 = 2 times per week and b2 = 3 times per week; with 3 repetitions. The results show that the a0b2 treatment (20 ml of concentrate / 200 ml of water with fumigation 3 times a week) was the best treatment because it presented the greatest increases in both total height (112 cm) and diameter (14.8 mm).